A widespread accessory protein family diversifies the effector repertoire of the type VI secretion system spike - Jake Colautti; Huagang Tan; Nathan P. Bullen; Stephanie S. Thang; Dirk Hackenberger; Andrew C. Doxey; John C. Whitney (Nature Communications)
Abstract Type VI secretion systems (T6SSs) are macromolecular assemblies that deliver toxic effector proteins between adjacent bacteria. These effectors span a wide range of protein families that all lack canonical signal sequences that would target them for export. Consequently, it remains incompletely understood how conserved structural components of the T6SS apparatus recognize a diverse repertoire of effectors. Here, we characterize a widespread family of adaptor proteins, containing the domain of unknown function DUF4123, that enable the recognition and export of evolutionarily unrelated effectors. By examining two nearly identical paralogs of the conserved T6SS spike protein, VgrG, we demonstrate that each spike protein exports a structurally unique effector. We further show that the recruitment of each effector to its respective spike protein requires a cognate adaptor protein. Protein–protein interaction experiments demonstrate that these adaptor proteins specifically tether an effector to a structurally conserved but sequence divergent helix-turn-helix motif found at the C-terminus of its cognate VgrG. Using structural predictions and mutagenesis analyses, we elucidate the molecular contacts required for these interactions and discover that these adaptor proteins contain a structurally conserved N-terminal lobe that has evolved to bind VgrG helix-turn-helix motifs and a structurally variable C-terminal lobe that recognizes diverse effector families. Overall, our work provides molecular insight into a mechanism by which conserved T6SS components recognize structurally diverse effectors.